Novaya abtomatizirovannaya sistema optimizatsii ratsionov pitaniya sportsmenov - Artemyeva, N. K. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study mathematical model of the athletes' nutritions ration's optimization. This model was realized in the programmed ensurance of IBM - cooperated computers and had allowed to solve the next problems: - to analyze the diurnal ration or separate food's intakes with the certain complex of the prepared food-stuffs, taking into consideration their energetical worth and chemical composition; - to calculate the optimal number for the fixed list of the prepared food-stuffs, maximally approached to the standard ration, recommended to the sporting specialization, to the energetic direction of the loadings, general conditions and special problems of the training process; - to optimize the ration taking into consideration the necessary parameters of the food-stuffs quality; - to convert the given quantatives of the ration's prepared food-stuffs into the set of market components, taking into consideration the losses when culinary processing; - to adjust the athletes' nutrition ration.